2000
DOI: 10.1016/s0168-1923(00)00195-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of vegetation in the San Pedro River basin area

Abstract: Changes in climate and land management practices in the San Pedro River basin have altered the vegetation patterns and dynamics. Therefore, there is a need to map the spatial and temporal distribution of the vegetation community in order to understand how climate and human activities affect the ecosystem in the arid and semi-arid region. Remote sensing provides a means to derive vegetation properties such as fractional green vegetation cover (fc) and green leaf area index (GLAI). However, to map such vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 11 publications
0
90
0
1
Order By: Relevance
“…The addition of the NDVI and soil characteristics in addition to microwave observations to these models reduced the RMSE for soil moisture retrieval by 30% approximately. This also opens the discussion for use of more sophisticated vegetation indices such as Fractional Green Vegetation Cover, Green Leaf Area Index, and Soil Adjusted Total Vegetation Index [63,64] to differentiate vegetation and soil response in soil moisture retrieval using microwave remote sensing data. Validation results showed that fuzzy logic and neural network models performed better compared to multiple regression.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the NDVI and soil characteristics in addition to microwave observations to these models reduced the RMSE for soil moisture retrieval by 30% approximately. This also opens the discussion for use of more sophisticated vegetation indices such as Fractional Green Vegetation Cover, Green Leaf Area Index, and Soil Adjusted Total Vegetation Index [63,64] to differentiate vegetation and soil response in soil moisture retrieval using microwave remote sensing data. Validation results showed that fuzzy logic and neural network models performed better compared to multiple regression.…”
Section: Discussionmentioning
confidence: 99%
“…SMA with fixed or variable endmembers has been used for the estimation of FVC in various environments including arid/semi-arid regions [21][22][23][24] and at scales from regional to global [25][26][27][28]. For grassland, linear SMA models with two endmembers (vegetation and non-vegetation) or three endmembers (live grass, senesced grass and soil) are effective in estimating endmember fractions due to their simplicity and interpretability [2][3][4]13,29].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies use a vegetation index (VI) as a signal or signature to maximize the differences among the endmembers. For example, NDVI based SMA has been used to estimate FVC in a large number of landscapes with various remote sensing data sources [26,[33][34][35]. However, NDVI has been criticized because FVC tends to be overestimated as it approaches certain proportions [36], especially in moderately vegetated areas [1,37].…”
Section: Introductionmentioning
confidence: 99%
“…Climate variability has a large impact on terrestrial ecosystems and aboveground biomass production (Qi et al 2000;Nemani et al 2003;Fabricante et al 2009;García-Romero et al 2010). Vegetation, as an important component of terrestrial ecosystems, links pedosphere, atmosphere, and hydrosphere of the Earth's system (Salim et al 2008;Zhong et al 2010).…”
Section: Introductionmentioning
confidence: 99%